Mechanical properties of Cold Recycled Bituminous Mixes with Crumb Rubber. Issue 10 (February 2019) - Castro, Andrea; Preciado, Jaime; Martinez-Arguelles, Gilberto; Fuentes, Luis; Dugarte, Margareth
Abstract: Cold mix recycling technologies based on asphalt emulsion have been acknowledged for allowing to reduce the environmental burdens associated with road pavement maintenance and rehabilitation. In fact, mixing and placement are conducted at lower temperatures leading to energy savings, a reduction of asphalt aging, fume and odour releasing, and a general decrease of airborne emissions. However, there are still several concerns related to the high variability of reclaimed asphalt pavement (RAP), the lack of standard mix-design procedures and the fair/low mechanical performance often achieved especially due to poor moisture resistance. On other side, the addition of crumb rubber into hot mix asphalts is considered an environmentally-friendly and cost-effective practice in several countries. Producing bituminous cold mixes containing crumb rubber to develop a "greener" paving material with a performance level comparable to that of conventional materials, represents a great challenge to materials engineering. This paper presents the results of a laboratory investigation concerning the mixdesign characteristics of cold 100%-recycled asphalt emulsion mixes, using crumb rubber to improve cold recycling engineered properties. Mechanical and volumetric properties were assessed through dynamic modulus and indirect tensile strength on dry and water-conditioned specimens.